Why is production of animal source foods important for economic development in Africa and Asia? - Baltenweck, Isabelle; Enahoro, Dolapo K.; Frija, Aymen; Tarawali, Shirley A. (Oxford University Press, 2020)
Production of animal source foods contributes to economic development by generating income and employment for livestock keepers and actors along livestock value chains. In Africa and Asia, their production cannot be analyzed without considering the other functions of livestock: livestock are an asset, a store of wealth for resilience and a factor of production in mixed farms. Local livestock production increases the availability of animal source foods as a source of proteins and micronutrients, necessary for a healthy population. Livestock provide a pathway to women empowerment and gender equality, which are important factors for economic development.